2020
DOI: 10.1088/1752-7163/ab6229
|View full text |Cite
|
Sign up to set email alerts
|

Topical review on monitoring tetrahydrocannabinol in breath

Abstract: Legalization of cannabis for recreational use has compelled governments to seek new tools to accurately monitor Δ9-tetrahydrocannabinol (Δ9-THC) and understand its effect on impairment. Various methods have been employed to measure Δ9-THC, and its respective metabolites, in different biological matrices. Recently, breath analysis has gained interest as a non-invasive method for the detection of chemicals that are either produced as part of biological processes or are absorbed from the environment. Existing bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Our findings are consistent with others who have shown that ∆ 9 -THC can be detected in breath up to several days since last use 9 , 10 . Because the leading technologies for breath-based testing for recent cannabis use 9 , 21 rely solely on the detection of ∆ 9 -THC, this could potentially result in false positive test outcomes due to the presence of ∆ 9 -THC in breath outside of the impairment window. It may be that other cannabinoids such as ∆ 9 -THCV and CBC, which were detected in breath only during the impairment window in the present study, are more suitable key indicators of recent cannabis use associated with impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with others who have shown that ∆ 9 -THC can be detected in breath up to several days since last use 9 , 10 . Because the leading technologies for breath-based testing for recent cannabis use 9 , 21 rely solely on the detection of ∆ 9 -THC, this could potentially result in false positive test outcomes due to the presence of ∆ 9 -THC in breath outside of the impairment window. It may be that other cannabinoids such as ∆ 9 -THCV and CBC, which were detected in breath only during the impairment window in the present study, are more suitable key indicators of recent cannabis use associated with impairment.…”
Section: Discussionmentioning
confidence: 99%
“…[68] Tang et al [69] reviewed the applications of nanostructured metal sulfide materials for sensing of VOCs and inorganic gases such as CO 2 , NH 3 , H 2 S, SO 2 , CH 4 , H 2 and nitric oxide. Recent advances in the role of eNoses in phenotyping of COPD were reviewed by Searlata et al [70] Mirzaei et al [71] review and compare devices used for D9-tetrahydrocannabinol detection in EB such as field asymmetric ion mobility spectrometry, semiconductor-enriched single-walled carbon nanotube chemiresistors, LC-MS/MS, microfluidic-based artificial olfaction, and optical-based gas sensing. They reported that amongst the examined platforms, from the portability and usability perspectives, optical-based, singlewalled carbon nanotube chemiresistors, and artificial olfaction are the most promising, whereas field asymmetric ion mobility spectrometry and LC-MS/MS are best suited for highly sensitive and selective testing with toxicology lab confirmation.…”
Section: Other Methodsmentioning
confidence: 99%
“…The laboratory chemical analysis of these matrices involves an extraction step followed by analysis using highly robust analytical techniques, such as gas chromatography–mass spectrometry (GC–MS) or liquid chromatography–tandem mass spectrometry (LC–MS/MS). The relevant sampling and analytical methods are described in more detail elsewhere (Mirzaei et al, 2020).…”
Section: Testing Matrices and Methodsmentioning
confidence: 99%